2014
DOI: 10.1016/j.ajog.2014.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum serpin B7 is associated with early spontaneous preterm birth

Abstract: Objective To identify serum biomarkers of early spontaneous preterm birth (SPTB) using semi-quantitative proteomic analyses. Study Design Nested case-control study of pregnant women with previous SPTB. Maternal serum was collected at 19 to 24 and 28 to 32 weeks gestation, and analyzed by liquid chromatography-multiple-reaction monitoring-mass spectrometry. Targeted and shotgun proteomics identified 31 candidate proteins that were differentially expressed in pooled serum samples from spontaneous preterm (<34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…Patients with SPTB also had high levels of INFG, this result being consistent with the findings of Curry et al 2008 in which high levels of INFG was observed in the PTB group [9] . High levels of MCP-3 were found in patients with PTB, this confirms the report by other studies in which the protein levels differ between the preterm and term in maternal plasma [16,17,22] . A high level of fractalkine was reported in pregnancy complicated with chorioamnionitis [23] .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Patients with SPTB also had high levels of INFG, this result being consistent with the findings of Curry et al 2008 in which high levels of INFG was observed in the PTB group [9] . High levels of MCP-3 were found in patients with PTB, this confirms the report by other studies in which the protein levels differ between the preterm and term in maternal plasma [16,17,22] . A high level of fractalkine was reported in pregnancy complicated with chorioamnionitis [23] .…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, animal research of anti-TNFA therapy has been shown to decrease foetal deaths and preterm deliveries in LPS-induced model of PTB [19] . In our samples, high levels of IL16, INFG, MCP-3, IL17, and fractalkine were seen among women with SPTB, which is similar to other reports in different ethnic groups [9,[16][17][18][19][20][21][22][23][24] . Patients with SPTB also had high levels of INFG, this result being consistent with the findings of Curry et al 2008 in which high levels of INFG was observed in the PTB group [9] .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Концентрация одного из белков, серпина В7 -в пробах сыворотки, взятой в срок 28-32 нед, была выше в среднем в 1,5 раза у женщин с последующими СПР по сравнению с контрольным вариантом. Единственного ис-следования для оценки негативного последствия повы-шенной концентрации серпина В7 в сыворотке крови бе-ременных недостаточно, и целесообразна проверка полу-ченных результатов на больших выборках [20]. Интересна работа M. Esplin и соавт.…”
unclassified